Surgical Treatment of Colorectal Cancer Asian Perspectives on Optimization and Standardization (Springer Singapore, 2018)
This book presents an Asian perspective on how the treatment of colorectal cancer can be optimized and standardized in ways that take into account technological advances and the trend towards individually tailored therapy. Readers will find careful, well-illustrated descriptions of the standard surgical techniques for rectal cancer and colon cancer that have contributed to recent improvements in 5-year survival rates in the Asia-Pacific region, where the incidence of colorectal cancer has been rising alarmingly due to lifestyle changes. The vital role now being played by minimally invasive laparoscopic and robotic options receives detailed scrutiny. Extent and timing of surgery, patient safety, risk of complications, and unresolved issues are all discussed. Furthermore, the use of surgery within the context of multimodal management including chemotherapy and radiotherapy is explained and an integrated approach for stage IV and recurrent disease is described. The book will serve as a valuable reference for young surgeons who are in training, experienced practitioners who want to enhance their knowledge and skills, and all others who wish to learn about this field.